Mother-Infant Attachment Style as a Predictor of Depression among Female Students - Rozita Amani; Mohammad Reza Majzoobi; Sedighe Azadi Fard (Mashhad University of Medical Sciences, 2017)
Background and aim: There are an increasing number of studies showing an association of adult attachment styles to psychopathology. Therefore, the purpose of the present study was to investigate the relation between attachment style and depression among students of Bu-Ali Sina University in Iran. Methods: This descriptive correlational study was conducted on 157 girl students who were randomly selected. They were evaluated by demographic questionnaire, Adult Attachment Inventory (AAI) (Hazan and Shaver), and theBeck Depression Inventory (BDI-II). The data was analysis by using Pearson correlation coefficient and regression analysis in SPSS 16 statistical package. Results: Findings indicated that secure attachment style had no significant correlation with depression and insecure attachment styles had a significant positive correlation with depression (p